Era 4.0: Tabir Layanan Bimbingan dan Konseling Berbasis Teknologi: 4.0: The Veil of Technology-Based Guidance and Counseling Services - Sarah Shafa Zahrani; Aswar, Aswar (Litera Academica Publishing, 2024)
Guidance and counseling is an effort to help students or counselees to be able to face problems and achieve successful, independent, happy, prosperous, and optimal self-development tasks in their lives. Era 4.0 is a veil of guidance and counseling services that are now technology-based because technology in era 4.0 is developing very rapidly, causing changes in the field of education, including guidance and counseling. The research method used is a literature study of the concepts discussed based on literature sourced from relevant scientific articles and journals. Today, the provision of guidance and counseling services is not only carried out through conventional methods such as direct face-to-face, but can also be combined with technology which in addition to making it easier will also provide new breakthroughs such as variations in the provision of guidance and counseling services through interactive, interesting, and not tied to location but still prioritizing the code of ethics and principles of implementing guidance and counseling. Guidance and counseling must always be in line with technology so that guidance and counseling still exist and exist. However, it cannot be denied that the application of technology in guidance and counseling services is accompanied by various challenges that need to be overcome so that technology-based guidance and counseling services can produce optimal services for students. Thus, as a counseling teacher, you must be able to develop your competencies and skills, both in guidance and counseling services and also in the application of technology.